Best Practices in Mainstreaming Environmental and Social Safeguards into Gas Pipeline Projects : Learning from the Bolivia-Brazil Gas Pipeline Project - Quintero, Juan (World Bank, Washington, DC, 2014)
This paper presents the Bolivia-Brazil Pipeline Project (GASBOL) as a case study for environmental and social safeguards analysis. The primary purpose of the GASBOL project was to supply the Brazilian market with Bolivian gas. The pipeline runs from Rio Grande, Bolivia, to Porto Alegre, Brazil, a distance of 3,150 kilometers. The Project faced significant environmental, social and institutional complexities stemming in part from its bi-national scope, it size and scale, and the fact that it had to deal with two legislative frameworks, inequalities in infrastructure, complex institutional agreements, indigenous communities, and sensitive ecological areas. Despite these considerable challenges, the design, construction, implementation, and operational phases of the project were well managed and as a result GASBOL has established itself as a benchmark for the management of large infrastructure projects. The project's innovative approach to environmental protection and social support resulted in a number of good practices and they are outlined in this paper. It also discusses several lessons learned from both successes and shortcomings of the project.